Spleen-Preserving Surgery in Splenic Artery Aneurysm - Ulaş Aday; Emre Bozdağ; Ebubekir Gündeş; Selçuk Gülmez; Kamuran Cumhur Değer (Case Reports in Surgery)
Endovascular interventions are increasingly used in the treatment of a splenic artery aneurysm (SAA), which is a rare and life-threatening clinical disorder. However, in cases of SAA rupture, minimally invasive interventions are unsuitable, and open surgery remains the gold standard method. In open surgery, care should be taken to preserve the spleen and its immune function in cases where an arterial segment of sufficient length allows for reconstruction. An SAA was detected in a 51-year-old woman who presented to our polyclinic with left upper quadrant pain. An endovascular intervention was unsuccessful, and open surgery was performed. Approximately 5 cm of aneurysm in the middle segment of the splenic artery was treated by arterial anastomosis, and the spleen was preserved. The patient experienced no postoperative complications and remained asymptomatic at the seventh month of follow-up. The aim of this case report is to emphasize the importance of splenic sparing surgery in cases of SAAs.